Outcome and failure patterns of localized sinonasal lymphoma in cats treated with first‐line single‐modality radiation therapy: A retrospective study. (9th July 2019) - Meier, Valeria S.; Beatrice, Laura; Turek, Michelle; Poirier, Valerie J.; Cancedda, Simona; Stiborova, Katerina; Körner, Maximilian; Marconato, Laura; Weyland, Mathias S.; Rohrer Bley, Carla
Abstract: Failure rate and site are not well defined in localized sinonasal lymphoma in cats treated with radiotherapy. In this study, we describe (a) failure pattern, (b) outcome, (c) influence of previously reported prognostic variables on the outcome in cats with suspected localized sinonasal lymphoma. In this multi‐institutional retrospective study, we included 51 cats treated with single‐modality radiotherapy. Cats were irradiated using 10x4.2Gy (n = 32), 12x3Gy (n = 11) or 5x6Gy (n = 8). Regional lymph nodes were prophylactically irradiated in 24/51 cats (47.1%). Twenty‐five cats (49.0%) developed progressive disease: progression was local (nasal) in five (9.8%), locoregional (nodal) in two (3.9%), local and locoregional in three (5.9%), systemic in nine (17.6%) and both local and systemic in six cats (11.8%). No cat receiving prophylactic nodal irradiation had progression in the locoregional lymph nodes. The median time to progression was 974 days (95%CI: 283;1666), with 58% and 53% of cats free of progression at 1 and 2 years, respectively. Median overall survival was 922 days (95%CI: 66;1779) with 61% and 49% alive at 1 and 2 years, respectively. Half of the cats that died of relapse/progression (13/26) died within 6 months of treatment, suggesting possible shortcomings of staging, rapid dissemination of disease or sequential lymphomagenesis. None of the prognostic factors evaluated were predictive of outcome (prednisolone use, anaemia, nasopharyngeal involvement, modified canine Adams tumour stage, protocol, total dose). Radiotherapy is an effective treatment for localized sinonasal lymphoma with a long time to progression. However, in one‐third of the cats, systemic disease progression occurs soon after radiotherapy.